New record and first description including SEM and μCT of the rare priapulid Acanthopriapulus horridus (Priapulida, Scalidophora) - Schmidt-Rhaesa, Andreas; Cañete Aguilera, Juan Ivan; Mutschke Orellana, Erika E. (My University, 2022)
We report a specimen of the rare priapulid Acanthopriapulus horridus from the Magellan Strait in Chile. This species, characterized by a conspicuous spine-covered caudal appendage, is distributed along the South American coast from Rio de Janeiro (Brazil) to the Magellan Strait, but only six specimens have been reported so far. This is the first documentation using scanning electron microscopy (SEM) and mu CT. Our investigation confirms and extends most reported results from previous publications. We show that the scalids on the introvert, although more loosely arranged than in other priapulids, occur in repeated series of decreasing size. Scalids and the different papillae on the trunk are sensory structures with apical tube-like openings. The spines on the caudal appendage have an apical opening, but pores instead of tube-like receptor openings. Pharyngeal teeth appear to be of two types in different regions of the pharynx. The caudal appendage is a strongly muscular organ, but its function remains unclear. (C) 2022 Published by Elsevier GmbH.
Keywords: chilean biodiversity; magellan benthos; priapulida; ecdysozoa; acanthopriapulus; mu ct; sem